Restitution of the UL56 gene expression of HSV-1 HFEM led to restoration of virulent phenotype: deletion of the amino acids 217 to 234 of the UL56 protein abrogates the virulent phenotype - Kehm, Roland; Rösen-Wolff, Angela; Darai, Gholamreza (Virus research, 1996)
Recently it was shown that the avirulent phenotype of HSV-1 strain HFEM is correlated to the lack of DNA sequences of the promoter region of the UL56 gene. In order to investigate the role of the UL56 gene of HSV-1 in the process of viral pathogenicity in more detail, a complete copy of the UL56 gene of the virulent HSV-1 strain 17 was inserted within the DNA sequences of the incomplete UL56 gene of the genome of HSV-1 strain HFEM. The UL56 gene of HSV-1 strain 17 comprises 1428 by corresponding to the nucleotide positions (NP) 115 967-117 395 of the genome of HSV-1 strain 17 (SacII-DNA fragment) containing the promoter region and the entire UL56 gene with identical transcription termination signals. This particular DNA fragment was inserted into the corresponding region of the genome of HSV-1 strain HFEM by co-transfection experiments in which the ß-galactosidase gene served as reporter gene. Those recombinant viruses with the ability to express the UL56 gene were tested for their pathogenicity in vivo. The results of these experiments indicate that the restoration of the viral UL56 gene expression led to the restitution of the virulent phenotype of HSV-1 strain HFEM. The UL56 protein which has been shown to be a component of the virion possesses several characteristic signatures e.g. a hydrophobic domain at the carboxy-terminus between amino acid residues 217 and 234 (VFGVVAIVVVIILVFLWR). In order to investigate the role of this particular signature of the UL56 protein in the process of viral pathogenicity, site-specific mutagenesis was performed for removing the carboxy-terminus of the UL56 protein. The deleted region of the DNA sequences of the UL56 gene between NP 1122-1175 corresponds to NP 116 220-116 373 of the viral genome. The DNA sequences of the UL56 gene of virulent HSV-1 strain 17 and F were replaced by DNA sequences of the truncated UL56 gene by co-transfection experiments in which the ß-galactosidase gene served as a reporter gene. Those recombinant viruses with the ability to express the truncated UL56 gene were examined for their pathogenicity in vivo. The analysis revealed that the expression of the truncated UL56 protein (without hydrophobic domain 217-234 aa) was not sufficient for the maintenance of the virulent phenotype of HSV-1 strains.
Elektronische Reproduktion der Druck-Ausgabe 2. März 1999
Gesehen am 05.09.2024